Reduced enumeration effort, but not coarse taxonomic resolution, is sufficient to represent beta diversity patterns of stream benthic diatoms - Castro, Emanuela; Siqueira, Tadeu [UNESP]; Melo, Adriano Sanches; Bini, Luis Mauricio; Landeiro, Victor Lemes; Schneck, Fabiana (Elsevier, 2023)
The use of reduced enumeration effort and coarse taxonomic resolutions are potential strategies for cost-effective biomonitoring programs and biological assessments. We evaluated whether reduced enumeration efforts (i.e., subsets of counted valves per sample) and identification to the genus level are sufficient to recover beta diversity patterns of benthic diatom metacommunities. Diatoms were sampled in 90 riffles within nine near-pristine subtropical streams. We found that reduced enumeration efforts were suitable to depict patterns both in the compositions of the communities and in biotic heterogeneity among streams produced by the original dataset (i.e., species-level identifications and 500 valves counted per riffle, the local community). A total of 400 and 50 valves were necessary to obtain similar compositional patterns observed using full samples identified at the species level for presence-absence and abundance data, respectively. Furthermore, biotic heterogeneity patterns among streams were recovered with 200 valves per local community for both presence-absence and abundance data. Identification to the genus level only reflected species-level compositional patterns when abundance data were used. However, the use of genus was not effective in depicting biotic heterogeneity patterns, independent of the enumeration effort. These results indicate that it is possible to reduce enumeration efforts, but not taxonomic resolution, to detect subtle regional biodiversity patterns of benthic diatoms in subtropical streams not subjected to strong environmental gradients. This is especially important due to the financial challenges faced by ecological and applied monitoring programs in tropical regions.
Keywords: Metacommunity; Periphyton; Procrustes; Sampling effort; Subtropical stream; Taxonomic sufficiency